THE TRAINING OF RHODESIAN OFFICERS AT THE ROYAL MILITARY ACADEMY, SANDHURST - Coster, K.R. (Scientia Militaria - South African Journal of Military Studies, 2012)
The editorial in Militaria 9/1 of 1979 notes that Professor Dale’s research with regard to the South African Armed Forces and their link with the United Kingdom and the Commonwealth of Nations, 1910-1961, has revealed that few South Africans ever studied at Sandhurst. On the other hand he observes that Rhodesia has far more Sandhurst-qual ified officers.